2014
DOI: 10.1016/j.dnarep.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotides as nucleotide excision repair substrates

Abstract: The incorporation of ribonucleotides in DNA has attracted considerable notice in recent years, since the pool of ribonucleotides can exceed that of the deoxyribonucleotides by at least 10 to 20 fold, and single ribonucleotide incorporation by DNA polymerases appears to be a common event. Moreover ribonucleotides are potentially mutagenic and lead to genome instability. As a consequence, errantly incorporated ribonucleotides are rapidly repaired in a process dependent upon RNase H enzymes. On the other hand, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Nucleotide excision repair (NER), a multistep DNA repair process that excises bulky ultraviolet- (UV) or chemical-induced lesions, has been implicated to act as a backup pathway for ribonucleotide removal in RER-deficient bacterial cells 63,64 . However, ribonucleotides in DNA are a poor substrate for the human NER system in vitro and ribonucleotides are not efficiently removed by NER in human cells 65 .…”
Section: Removal Of Ribonucleotides From Dnamentioning
confidence: 99%
“…Nucleotide excision repair (NER), a multistep DNA repair process that excises bulky ultraviolet- (UV) or chemical-induced lesions, has been implicated to act as a backup pathway for ribonucleotide removal in RER-deficient bacterial cells 63,64 . However, ribonucleotides in DNA are a poor substrate for the human NER system in vitro and ribonucleotides are not efficiently removed by NER in human cells 65 .…”
Section: Removal Of Ribonucleotides From Dnamentioning
confidence: 99%
“…Furthermore, despite its small impact on the global helical properties of the DNA duplex, an isolated rNMP can be replaced as efficiently as various bulky DNA-distorting lesions. Based on the results of molecular dynamics simulations, Cai et al ., [52] have proposed that ribonucleotide recognition by the UvrAB relies on hydrogen bonding and electrostatic interactions of the ribose 2'-OH group with several aromatic residues in UvrB that are responsible for damage recognition.…”
Section: Backup Pathways Of Ribonucleotide Removalmentioning
confidence: 99%
“…In addition to the RNase H system employed for the removal of RNA from genomic DNA, topo I removes single rNMPs in S. cerevisiae and nucleotide excision repair (NER) can remove both single rNMPs and stretches of rNMPs in E. coli (Kim et al, 2011; Vaisman et al, 2013; Cai et al, 2014). In this section, we review the processes impacting removal of rNMPs incorporated into genomic DNA.…”
Section: 0 Removal Of Rnmps From Genomic Dnamentioning
confidence: 99%
“…In yeast, topoisomerase I removes single embedded rNMPs yielding a 2–5 bp deletion, which can be mitigated by helicase Srs2 in collaboration with Exo I (Kim et al, 2011; Sekiguchi and Shuman, 1997; Williams et al, 2013; Potenski et al, 2014). Woodgate and co-workers again used the frequent rNMP incorporation by UmuCY11A variant and found that nucleotide excision repair (NER) serves as a backup pathway for removal of rNMPs in cells deficient for rnhB [(Vaisman et al, 2013) for review (Cai et al, 2014)].…”
Section: 0 Removal Of Rnmps From Genomic Dnamentioning
confidence: 99%
See 1 more Smart Citation